2021
DOI: 10.1371/journal.pone.0251028
|View full text |Cite
|
Sign up to set email alerts
|

SPATS1 (spermatogenesis-associated, serine-rich 1) is not essential for spermatogenesis and fertility in mouse

Abstract: SPATS1 (spermatogenesis-associated, serine-rich 1) is an evolutionarily conserved, testis-specific protein that is differentially expressed during rat male meiotic prophase. Some reports have suggested a link between SPATS1 underexpression/mutation and human pathologies such as male infertility and testicular cancer. Given the absence of functional studies, we generated a Spats1 loss-of-function mouse model using CRISPR/Cas9 technology. The phenotypic analysis showed no overt phenotype in Spats1-/- mice, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…In rats, Spats1 attains maximum levels during meiosis of the first spermatogenic wave, mostly in pachytene spermatocytes, whereas the signal was weaker in spermatogonia, Sertoli cells, and myoid cells [ 20 ]. Despite the fact that Spats1 is a testis-specific protein, the Spats1 loss-of-function mouse model analysis revealed that knockdown of Spats1 did not affect fertility in either males or females [ 36 ]. The testis-specific expression of Spats1 and the expression pattern in different germ cells imply that Spats1 may be closely associated with testicular differentiation and male germ cell differentiation in P. sinensis .…”
Section: Discussionmentioning
confidence: 99%
“…In rats, Spats1 attains maximum levels during meiosis of the first spermatogenic wave, mostly in pachytene spermatocytes, whereas the signal was weaker in spermatogonia, Sertoli cells, and myoid cells [ 20 ]. Despite the fact that Spats1 is a testis-specific protein, the Spats1 loss-of-function mouse model analysis revealed that knockdown of Spats1 did not affect fertility in either males or females [ 36 ]. The testis-specific expression of Spats1 and the expression pattern in different germ cells imply that Spats1 may be closely associated with testicular differentiation and male germ cell differentiation in P. sinensis .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kastor and Polluks polypeptides encoded by lncRNAs were inserted in the outer mitochondrial membrane and directly interacted with voltage-dependent anion channel to regulate spermatogenesis [ 19 ]. Nevertheless, research has shown that single deletion of lncRNAs might have no significant effect on male fertility, suggesting the function of many lncRNAs in spermatogenesis may be redundant or fine-tuning [ 20 , 21 , 22 ]. Hence, more studies are needed to identify and uncover specific lncRNAs working on spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%